THE ROLE OF HOLISTIC MARKETING IN THE QUALITY OF BANKING SERVICES: APPLIED RESEARCH IN AL-TAIF ISLAMIC BANK - Assistant Teacher Saja Hussein Ahmed (Scholars Digest Publishing, 2024)
The study examined the importance of comprehensive marketing in enhancing the banking services provided by Al-Taif Islamic Bank to its customers. The study focuses on exploring the role of using holistic marketing techniques as a means of enhancing the quality of banking services. The research problem arose to identify the nature of the correlation between comprehensive marketing and the quality of banking service. The study also aimed to identify the role that comprehensive marketing plays in improving the quality of banking services at Al Taif Islamic Bank. The study was conducted on a purposive random sample of (64) bank employees. Data were collected by distributing a questionnaire, and statistical data analysis software was used(spss) to analyze the factors affecting the quality of banking services. The research results indicated that there is a strong and positive relationship between comprehensive marketing and the quality of banking services. The research provided recommendations for the bank to adopt comprehensive marketing strategies, which leads to improving the quality of services provided by the bank, providing ample information to customers regarding available banking products, and providing customer service around the clock, thus achieving customer satisfaction and loyalty and enhancing the bank’s competitive advantage in the market.
Keywords: holistic marketing, service quality, internal marketing, performance marketing, relationship marketing, integrated marketing.